Results of Transurethral Correction of Stenotic Developmental Abnormalities of Ureterovesical Junction in Children - Makhmudjon Aliev1, Akmal Rakhmatullaev1, Bilim Terebaev1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Purpose: Improving the results of treatment of stenotic developmental abnormalities of the ureterovesicaljunction (SDA UVJ) in children.Materials and Method: Treatment analyzed included 88 pediatric patients (125 ureters) with SDA UVJ,aged 3 months - 15 years.Results: Endoscopic stenting has been performed using antireflux stents, with subsequent bladder drainageusing a urinary catheter. We have also developed an inverted V-shaped ureterocele incision. The UVJ controlcalibration has been performed using calibration catheters. If the UVJ diameter did not correspond to theage norm, the second stage of treatment was carried out by dilating with conical bouges or by UVJ balloondilating. Transient complications developed in the immediate postoperative period have been successfullyeliminated using conservative measures, in all cases.Conclusions: The study results imply the effectiveness of endoscopic method in correcting SDA UVJ inchildren.